2021
DOI: 10.1021/acscatal.1c03474
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Chemoenzymatic Conversion of Alkynes to Chiral Amines

Abstract: A one-pot chemoenzymatic sequential cascade for the synthesis of chiral amines from alkynes was developed. In this integrated approach, just ppm amounts of gold catalysts enabled the conversion of alkynes to ketones (>99%) after which a transaminase was used to catalyze the production of biologically valuable chiral amines in a good yield (up to 99%) and enantiomeric excess (>99%). A preparative scale synthesis of (S)-methylbenzylamine and (S)-4-methoxy-methylbenzylamine from its alkyne form gave a yield of 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…51 Very recently, Rueping and co-workers have developed a hydration−biotransamination sequential approach to transform terminal arylacetylenes into optically active 1-arylethan-1-amines, combining gold(I) chloride and a stereoselective transaminase in a sequential manner since the substrate concentration had to be diminished and the temperature decreased after the hydration step. 52 Being aware of the difficulties to develop multicatalytic transformations when considering an alkyne hydration and biotransformation sequences in a concurrent cascade mode, 50−52 herein we have focused on the exploitation of the compatibility of an N-heterocyclic carbene (NHC)− gold(I) complex, namely, [1,3-…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Very recently, Rueping and co-workers have developed a hydration−biotransamination sequential approach to transform terminal arylacetylenes into optically active 1-arylethan-1-amines, combining gold(I) chloride and a stereoselective transaminase in a sequential manner since the substrate concentration had to be diminished and the temperature decreased after the hydration step. 52 Being aware of the difficulties to develop multicatalytic transformations when considering an alkyne hydration and biotransformation sequences in a concurrent cascade mode, 50−52 herein we have focused on the exploitation of the compatibility of an N-heterocyclic carbene (NHC)− gold(I) complex, namely, [1,3-…”
Section: ■ Introductionmentioning
confidence: 99%
“…Interestingly, hydration–bioreduction routes have also been reported, transforming terminal alkynes in optically active 1-arylethan-1-ols and aliphatic alcohols in sequential protocols. , In this context, Mihovilovic and co-workers have sequentially combined the action of AuCl 3 in 2-PrOH using 4 equiv of water for alkyne hydration at 65 °C with the bioreduction of the resulting 1-arylethan-1-one intermediates at 30 °C, while Lipshutz’ group described a one-pot sequential protocol including the use of (HandaPhos)­AuCl in the presence of a silver salt, trifluoroacetic acid, and a surfactant in water for the hydration step, adding the ADH, cofactor, buffer, and additional surfactant for the reductive step once the alkyne was consumpted . Very recently, Rueping and co-workers have developed a hydration–biotransamination sequential approach to transform terminal arylacetylenes into optically active 1-arylethan-1-amines, combining gold­(I) chloride and a stereoselective transaminase in a sequential manner since the substrate concentration had to be diminished and the temperature decreased after the hydration step …”
Section: Introductionmentioning
confidence: 99%
“…Rather than focus on palladium catalysis, attention turned to use of Au( i ), 7 as previous usage in micellar media has proven to be very effective in reactions of alkynes, such as hydrations. 8 Several ligated AuCl complexes were evaluated as catalysts for the targeted cyclization of 2-alkyne-substituted anilines (Fig. 2; also see the ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…ADH‐A from Rhodococcus ruber and Lk ‐ADH from Lactobacillus kefir they could access a set of chiral 1‐phenylethanol derivatives in moderate to excellent conversions and in high ee . This process has now also been extended to the preparation of chiral amines using AuCl as the catalyst for the hydration step at very low loadings (0.2 mol%) in combination with different ω‐transaminases to afford the corresponding enantioenriched α‐methylbenzylamines (Scheme 4b) [53] . Following a similar strategy, Chang et al .…”
Section: Linear Cascades Combining Transition Metal Catalysis and Bio...mentioning
confidence: 99%
“…This process has now also been extended to the preparation of chiral amines using AuCl as the catalyst for the hydration step at very low loadings (0.2 mol%) in combination with different ω-transaminases to afford the corresponding enantioenriched α-methylbenzylamines (Scheme 4b). [53] Following a similar strategy, Chang et al have recently reported the combination of gold-catalysed alkyne hydration of propargyl ethers followed by bioreductive amination employing the amine dehydrogenase from Geobacillus kaustophilus (GkAmDH) to access a broad set of chiral aryloxy-and alkyloxy-propan-2-amines. [54] Due to compatibility issues, the Au/carbene catalyst (IPrAuOTf) was encapsulated in mesoporous silica, allowing the efficient implementation of both steps in the same vessel.…”
Section: Recent Examples Of Synthetic Cascades Combining Other Tm-med...mentioning
confidence: 99%